Assessment of polycyclic aromatic hydrocarbons in particulate matter collected from exhaust of vehicles. - Retiracion, Pilar Mercedes A. (University of the Philippines Visayas, 2016)
In this study, analysis of polycyclic aromatic hydrocarbons (PAHs), a component of particulate matter, which is one of the major categories of pollutants, was done in soot collected from the exhaust of vehicles. Four types of vehicles were considered : diesel-fueled bus and jeepney, and gasoline-fueled motorcycle and car/SUV. Samples were prepared for analysis using modifiedEPA-8270-C determination of semi volatile compounds. Extracts were subjected to gas chromatography-mass spectrometry analysis. Total ion chromatograms (TIC) of the 16 US Environmental protection Agency PAHs were iniitially produced and these were further examined by generating the extracted ion chromatograms (EIC). Confirmed PAH peaks were integrated and plotted to the calibration curves of the prepared external standards to calculate the concentrations of the PAHs. Results showed that nine PAHs were detected, in various concentrations. Jeepneys have higher levels of PAH compared to buses, while motorcycles and cars/SUV do not differ significantly.